Urban Industrial Land Expansion and Its Influencing Factors in Shunde: 1995–2017. (25th September 2020) - Xiong, Chen; Lu, Jiayi; Niu, Fangqu
Abstract : The change in the industrial land is of great significance to the sustainable development of cities. However, scholars have done relatively little research on this subject, especially on the urban industrial land expansion process and its influencing factors. This article selects Shunde, a typical Chinese industrial city of the Guangdong province, using remote sensing interpretation to analyze the spatiotemporal evolution of industrial land expansion from 1995 to 2017 and applies the multiple regression model to analyze the influencing factors. The main conclusions are as follows: the industrial land in Shunde has experienced the development trend of "slow expansion-rapid expansion-slow expansion, " and the "fragmentation" of the industrial land space is still prominent. Decentralization, marketization, capital, and labor force have passed the significance test of the model, which are important factors influencing the expansion of the industrial land in Shunde. Among them, decentralization is the primary factor, while marketization has the greatest impact on industrial land expansion in Shunde. The influence of globalization and technical progress is not significant.